All Days 2010
DOI: 10.2118/135723-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Flow Splitting in Parallel/Looped Pipelines

Abstract: A novel and unique experimental facility was design, constructed and instrumented, enabling slug flow splitting data acquisition in both parallel and looped lines. A total of 81 experimental test runs were carried out for various superficial gas and liquid velocity combinations. Uneven split conditions data were acquired by utilizing either a choke valve on one of the lines or different pipe diameters. For the symmetrical configurations of both parallel and looped equal diameter lines, the phases split equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…El-Shaboury et al [8] studied the shunt of stable two-phase flow (stratified flow, wavy flow and annular flow) at an impact T-tube. Alvarez et al [9] conducted slug flow experiments. These two studies showed that by keeping the downstream equipment operating under the same conditions, the GLTPF always exhibited a uniform distribution, independent of the flow pattern at the inlet.…”
Section: Introductionmentioning
confidence: 99%
“…El-Shaboury et al [8] studied the shunt of stable two-phase flow (stratified flow, wavy flow and annular flow) at an impact T-tube. Alvarez et al [9] conducted slug flow experiments. These two studies showed that by keeping the downstream equipment operating under the same conditions, the GLTPF always exhibited a uniform distribution, independent of the flow pattern at the inlet.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, scholars have carried out a lot of research work on the gas-liquid two-phase flow split at the T-junction. El-Shaboury et al [5] investigated the flow patterns of stratified, wavy and annular flow splitting at the impacting tee and Alvarez et al [6] conducted experiment with slug flow. Mi et al [7] studied the shunt characteristics of slug flow from a single pipe into a parallel separator.…”
Section: Introductionmentioning
confidence: 99%
“…Due to operational reasons, the production of a wellpad has to be routed to one and only one tank battery. This assumption follows from: (1) contract conditions with the land owners, (2) flow measuring and integrity requirements, and (3) difficulties when splitting a three-phase flow with unsteady pressure conditions (Azzopardi and Smith 1992;Alvarez et al 2010;Worthen and Henkes 2015). The difficulty of the problem increases with the number of wellpads, and in practice, the straightforward solution is to increase the number of tank batteries (TB), even though they become underutilized in a few months when the wells production declines.…”
Section: Introductionmentioning
confidence: 99%